Exploring the gender gap in achievement in Malaysia: a case for learning styles - Dahlan, Nadia Ainuddin; Md. Noor, Nor Azian; Syed Mustafa, Sharifah Muzlia; Said Hashim, Khadijah; Zulkifli, Voviana (Common Ground Publishing, 2010)
a common problem shared by many institution of higher learning around the world today is the wide discrepancy in the enrollment of males and females.although the gender gap inpublic universities has been widely highlited in malaysia.it is believed this problem may be inextricably linked to gender differences in achievement at the school level.it has been suggested that accommodating gender differences in learning styles in school could help bridge the gender gap.therefore,this study attempted to identify the extent of the gender gap by comparing the self-reported results of a national standardized test,the lower secondary examination or penilaian menengah rendah(PMR) of 411 form four students from four secondary schools in kuala lumpur.respiondents also completed the felder and soloman (1991) index of learning styles(ILS)which determined their learning styles on four subscales:active-reflective, sensing-intuitive, visual-verbal and sequential-global.the study found a significant gender difference in achievement but not for learning styles.the majority of respondent were active,visual and sequential-global.the study found a significant gender difference in achievement but not for learning styles.the majority of respondents were active,visual and sequential.however,a binary logistic regression model found gender,sensing and visual learning styles to be significant predictors of achievement.therefore,accommodating these learning styles in particular,may promote the academic achievement of students.future teachers should consequently be equipped with practical knowledge of learning styles in the hope of increasing achievement across genders,thus narrowing the gender gap in schools and lead to more gender-balanced university classrooms capable of nurturing quality human capital amongst both women and men.